Pediatric pulmonary valve replacements: Clinical challenges and emerging technologies - Matthew Crago; David S. Winlaw; Syamak Farajikhah; Fariba Dehghani; Sina Naficy (Wiley, 2023)
Abstract Congenital heart diseases (CHDs) frequently impact the right ventricular outflow tract, resulting in a significant incidence of pulmonary valve replacement in the pediatric population. While contemporary pediatric pulmonary valve replacements (PPVRs) allow satisfactory patient survival, their biocompatibility and durability remain suboptimal and repeat operations are commonplace, especially for very young patients. This places enormous physical, financial, and psychological burdens on patients and their parents, highlighting an urgent clinical need for better PPVRs. An important reason for the clinical failure of PPVRs is biofouling, which instigates various adverse biological responses such as thrombosis and infection, promoting research into various antifouling chemistries that may find utility in PPVR materials. Another significant contributor is the inevitability of somatic growth in pediatric patients, causing structural discrepancies between the patient and PPVR, stimulating the development of various growth‐accommodating heart valve prototypes. This review offers an interdisciplinary perspective on these challenges by exploring clinical experiences, physiological understandings, and bioengineering technologies that may contribute to device development. It thus aims to provide an insight into the design requirements of next‐generation PPVRs to advance clinical outcomes and promote patient quality of life.